Improving European policy to support cancer survivors. (May 2018) - De Lorenzo, F.; Apostolidis, K.; Florindi, F.; Makaroff, L.E.
Highlights: Often, cancer survivors are left unchecked and not followed up properly after the end of the acute treatment phase. It is important to develop national plans to ensure that the healthcare system can fully support cancer survivors' needs. The European Guide on Quality Improvement in Comprehensive Cancer Control provides survivorship care plan guidelines. Survivorship care plans must ensure that survivors can be reintegrated in the workforce, according to their needs. Patient organisations can serve as catalysts to amplify the voices of people with cancer when developing policy. Abstract: Due to increasing investment in health, earlier diagnosis, timely treatment, and new therapies, more people are surviving a diagnosis of cancer. While it is encouraging to observe a substantially increase in the number of cancer survivors, people with acute cancer, those with chronic cancer, and those cured of cancer all have different needs and preferences. The "European Guide on Quality Improvement in Comprehensive Cancer Control", produced by the European Commission's Joint Action on Cancer Control, includes a specific chapter on survivorship. This chapter was developed in collaboration with patient organisations, and provides a set of recommendations for the development of quality national survivorship care plans. Patient organisations have demonstrated the ability to link the policy environment to the reality of cancer care. For example, the "Patient Guide on Survivorship", produced by the European Society for Medical Oncology in collaboration with the European Cancer Patient Coalition, is the first practical implementation of the Joint Action on Cancer Control survivorship recommendations. The guide provides actionable information on follow-up care, setting the foundation for a personalised survivorship care plan. A checklist of key interventions completes the document. Exercise, increased fruit and vegetable consumption, smoking cessation, and cognitive behavioural therapy have all demonstrated beneficial effects on the lives of cancer survivors. This guide is a practical tool to empower people with cancer to engage with their healthcare team. The return to an active and normal life, for all cancer survivors who can reasonably achieve this goal, must be a priority of all healthcare systems.